Secure Overlay Cloud Storage with File Assured Deletion - T.P. Suryachandra Rao, Dayananda RB, G.Manoj Someswar (International Journal of Scientific Research and Management (IJSRM), 2015)
In our research paper, we present policy-based file assured deletion, the major design building block of our FADE architecture. Our main focus is to deal with the cryptographic key operations that enable file assured deletion. We first review time-based file assured deletion. We then explain how it can be extended to policy-based file assured deletion.